Civic engagement in the Indonesia health sector: The role of religiosity, empathy, and materialism attitude. Issue 4 (21st November 2019) - Pratono, Aluisius Hery; Djoemadi, Firman Rosjadi; Avanti, Christina; Sinaga, Nur Flora Nita Taruli Basa; Maharani, Asri
Abstract : Purpose: The purpose of this paper is to understand the impact of religiosity on civic engagement in the health sector through giving advocacy for people with AIDs, mental health, cancer and disability. Design/methodology/approach: The authors achieve this aim by proposing a structural equation model, which was derived based on literature. The data collection involved an on-line purposive sampling survey, which targeted young people who intend to work in the health sector. The survey asked about the experience and perception of 610 respondents in Indonesia. Findings: The results indicate that the respondents with high religiosity were identified to be more caring towards those who suffer from mental health, AIDs, cancer and disability. However, the highly religious were less motivated by empathy in conducting civic engagement in the health sector. In this study, the impact of religiosity on civic engagement was found to be stronger for those who identified with low materialism. Originality/value: The study contributes to the discussion on altruistic theory by challenging the widespread assumption that feelings of empathy drive civic engagement. The results extend the discussion on how to promote civic engagement in the health sector for young people with high materialism attitude.